Analisis Kesulitan Belajar Matematika terhadap Siswa Keluarga "Broken Home" di SMA Uswatun Hasanah Jakarta Timur - Mohamad Lutfi Nugraha (SAP (Susunan Artikel Pendidikan), 2019)
The purpose of this study is to find out the difficulties of learning mathematics students who have problems with their families or broken home. The place of this research is a private high school in East Jakarta, namely Uswatun Hasanah High School. The research sample is students who have problems outside of school, namely problems with their families. The method of this research is an exploratory survey with a qualitative approach. Data collection of this research are interviews, observations and documents from research subjects. Two broken home children were the subjects of this study. The results of this study indicate that the process of learning mathematics for students who are broken home needs special handling in the form of advice and enthusiasm from mathematics teachers, counseling teachers, and homeroom teachers and is expected to be given effective learning methods to make students more focused in learning and more mature in face the problem